Computer Science &Amp; Information Technology 2018
DOI: 10.5121/csit.2018.80705
|View full text |Cite
|
Sign up to set email alerts
|

Study on Augmented Context Interaction System for Virtual Reality Animation Using Wearable Technology

Abstract: Currently, the virtual reality market is receiving global attention, and VR animation entertainment content is attracting attention as a new content market. In this study, we successfully develop these kinds of VR animations by focusing on interactions, the largest feature of virtual reality content, and we present a novel interaction method for virtual reality animations. We created ".FLY," a virtual reality movie, using wearable technology, and designed augmented context interactions to verify the emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The study found that the use of AR significantly improved student understanding of physically‐based rendering concepts. Moreover, Reference 57 presented a novel interaction method for VR animations. They created “.FLY,” a VR movie, using wearable technology and designed augmented context interactions to verify the emotional empathy and emotional immersion effect of the active story‐based interactions experienced by the user in a VR environment.…”
Section: Impact Of New Technologies On Animationmentioning
confidence: 99%
“…The study found that the use of AR significantly improved student understanding of physically‐based rendering concepts. Moreover, Reference 57 presented a novel interaction method for VR animations. They created “.FLY,” a VR movie, using wearable technology and designed augmented context interactions to verify the emotional empathy and emotional immersion effect of the active story‐based interactions experienced by the user in a VR environment.…”
Section: Impact Of New Technologies On Animationmentioning
confidence: 99%